A model for understanding electromigration-induced void evolution in dual-inlaid Cu interconnect structures - Helonde, J. B. (2013)
Electromigration-induced void evolution in various dual-inlaid copper (Cu) interconnect structures was simulated by applying a phenomenological model assisted by Monte Carlo-based simulations, considering the redistribution of heterogeneously nucleated voids and/or pre-existing vacancy clusters at the Cu/dielectric cap interface during electromigration. The results indicate that this model can qualitatively explain the electromigration-induced void evolution observed during experimental in situ secondary-electron microscopy (SEM) investigations as well as in various other reported studies. The electromigration mechanism in Cu interconnect structures and differences in the peculiar electromigration-induced void evolution in various dual-inlaid Cu interconnect structures can be clearly understood based on this model. These findings warrant reinvestigation of technologically important electromigration mechanisms by developing rigorous models based on similar concepts.